A finite element study of fatigue load effects on total hip joint prosthesis. Issue 14 (10th November 2021) - Aghili, Seyed Arvin; Hassani, Kamran; Nikkhoo, Mohammad
Abstract: The main goal of this study was to perform a fatigue analysis and compare the results for different materials. A 72 years old patient was chosen and his hip radiographic/CT scan images were used to construct the geometry. We used four different material including Titanium, Titanium alloy, Cobalt-Chrome, and Stainless steel. The material characteristics of these prostheses were extracted from the literature. All models were exported to ANSYS software for mathematical analysis and the Von-Mises criteria, deformations, and the fatigue life were calculated for each material. Our findings showed that titanium prosthesis tolerated the lowest stress (i.e., 591 MPa for static, and 687 MPa for fatigue loading) and highest safety factor (i.e., 1.54). We found out that Titanium material could be used as the most appropriate one for the hip prosthesis due to lower stress concentration and longer life compared to other materials.